Pengaruh Media Gambar Seri Terhadap Kemampuan Bercerita Anak di Taman Kanak-Kanak Islam Shabrina Padang - Ulfa, Amalia; Rakimahwati, Rakimahwati (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2020)
The purpose of this study was to analyze how the influence of media image series on the ability to tell children in Islamic Kindergarten Shabrina Padang. This type of research is experimental research. The study was conducted at Shabrina Islamic Kindergarten. The sample in this study was group B1 and B2, each group consisting of 17 people and 18 poeple. Data analysis is normality test, homogeneity test and hypothesis test. The results obtained: 1) hypothesis pre-test value is tcount <ttabel where 0.097 <2.04841 as at the significant level α = 0.05 and dk = 33 this means the hypothesis Ha is rejected and H0 accepted, in the sense of the word that there is no significant difference between the results of the ability to tell of children who use serial image media as media in Islamic Kindergarten Shabrina Padang, and the results of the hypothesis test post-test values, namely tcount <ttabel where 2.185> 2 , 04841 at significant level α = 0.05 and dk = 28 this means that the hypothesis Ha is accepted and H0 is rejected, in the sense of the word that there is a significant difference between the ability to tell children using media image series as media in the Shabrina Islamic Kindergarten in Padang.